Application of microscopy technique and high-performance liquid chromatography for quality assessment of the flower bud of Tussilago farfara L. (Kuandonghua) - Li, Da (Pharmacogn Mag, 2015)
BACKGROUND: Quality control is one of the bottleneck problems limiting the application and development of traditional Chinese medicine (TCM). In recent years, microscopy and high-performance liquid chromatography (HPLC) techniques have been frequently applied in the quality control of TCM. However, studies combining conventional microscopy and HPLC techniques for the quality control of the flower bud of Tussilago farfara L. (Kuandonghua) have not been reported. OBJECTIVE: This study was undertaken to evaluate the quality of the flower bud of T. farfara L. and to establish the relationships between the quantity of pollen grains and four main bioactive constituents: tussilagone, chlorogenic acid, rutin and isoquercitrin. MATERIALS AND METHODS: In this study, microscopic examination was used to quantify microscopic characteristics of the flower bud of T. farfara L., and the chemical components were determined by HPLC. The data were analyzed by Statistical Package for the Social Sciences statistics software. RESULTS: The results of the analysis showed that tussilagone, chlorogenic acid, rutin and isoquercitrin were significantly correlated with the quantity of pollen grains in the flower bud of T. farfara L. There is a positive correlation between them. From these results, it can be deduced that the flower bud of T. farfara L. with a greater quantity of pollen grains should be of better quality. CONCLUSION: The study showed that the established method can be helpful for evaluating the quality of the flower bud of T. farfara L. based on microscopic characteristic constants and chemical quantitation.